Edible mayonnaise-like Pickering emulsion stabilized by pea protein isolate microgels: Effect of food ingredients in commercial mayonnaise recipe. (15th May 2022) - Li, Sisheng; Jiao, Bo; Meng, Shi; Fu, Weiming; Faisal, Shah; Li, Xiaomin; Liu, Hongzhi; Wang, Qiang
Highlights: A mayonnaise-like Pickering emulsion was stabilized by pea protein isolate microgels. NaCl increased droplet size and sucrose improved emulsion's viscosity. The plant-scaled egg-free mayonnaise has a 99.8% thixotropic recovery. Lab and plant produced emulsions have similar viscosity to commercial mayonnaise. Abstract: Particle stabilized O/W Pickering emulsion has great potential for making egg-free mayonnaise. In this study, we fabricated pea protein isolate (PPI) microgels by gel-breaking method and applied in mayonnaise-like Pickering emulsion. The effects of acetic acid (pH), sodium chloride (NaCl), and sucrose, which are typically used in commercial mayonnaise were studied. The minimum droplet size (47.0 μm) was found below isoelectric point. The NaCl decreased ζ-potential to almost 0 and risen droplet size to 75.9 μm. The sucrose enhanced the emulsion's viscosity while lowering thixotropic recovery rate. Based on droplet size, viscosity, thixotropic recovery, and microstructure; 350 mmol NaCl and 4 wt% sucrose was finally used to make egg-free mayonnaise-like Pickering emulsion, and showed similar properties compared with commercial mayonnaise, and the thixotropy recovery rate was near 100%. A plant-scale test further confirmed the feasibility. The results showed the PPI microgels had a strong application prospect to form egg-free mayonnaise.